Influence of subduction components on magma composition in back‐arc basins: a comparison between the Mariana and Okinawa troughs. (31st May 2016) - Zhao, Guangtao; Luo, Wenqiang; Lai, Zhiqing; Tian, Liyan; Xu, Cuiling
Abstract: New Sr, Nd, and Pb isotopic data of seven basalt samples from the middle Mariana Trough were analysed together with existing geochemical data of basalts from the middle Mariana Trough (MMT), the northern Mariana Trough (NMT), the middle Okinawa Trough (MOT), and the southern Okinawa Trough (SOT). Basalts from the Mariana and Okinawa troughs have similarities to island arc lavas and are enriched in large ion lithophile elements but depleted in high field strength elements compared with normal mid‐ocean ridge basalt (N‐MORB). The Sr, Nd, and Pb isotopic compositions of the back‐arc basin basalts maybe modelled by a mixing between end‐member components of N‐MORB‐like mantle and enriched mantle end‐member. Modelling results suggest that as the degree of back‐arc extension increases, the proportion of subduction components in the source magma decreases. The compositions of SOT basalts can be explained by the mixing of subduction components in the proportion 16%, followed by MOT at 14%, NMT at 7%, and MMT at 4%. This result indicates that the contribution of subduction components to the composition of source magmas for back‐arc basalts is closely related to the tectonic evolution of the entire back‐arc system. The proportions of subduction components in basaltic magma sources can be used as an indicator of the extent of evolution of a back‐arc basin or the development of a back‐arc spreading system. Copyright © 2016 John Wiley & Sons, Ltd.